2018
DOI: 10.25159/1998-8125/4345
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study on the Gender-Based Differences in Entrepreneurial Intention and Its Antecedents amongst Students of a South African University of Technology

Abstract: Although the prevailing gender-linked fissures in entrepreneurial activity are shrinking in African economies, a disturbing feature of the contemporary business start-up environment is that women persistently are less willing to engage in entrepreneurship compared to men. In addition, women focus more on low technology and service-oriented business activities, which yield relatively lower financial value than other economic sectors. Given the subtle but entrenched gender vulnerabilities and biases that constan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 38 publications
0
17
5
1
Order By: Relevance
“…Instead of finding higher entrepreneurial intentions in the business school, in which entrepreneurship education is more central, the study found that the students of the sports school had a greater tendency to start a business. The same is true in other industries, in which some studies have reported that male students have greater entrepreneurial intentions and seem to be more confident than women (Zarate-Hoyos and Larios-Meono, 2015; Bretones and Radrigan, 2018;Gavurova et al, 2018;Ndofirepi et al, 2018). However, it is not only female students who present lower levels of entrepreneurial intention but also students of both genders with no previous business experience (Hu and Ye, 2017).…”
Section: Clustereducation and Entrepreneurshipmentioning
confidence: 77%
See 1 more Smart Citation
“…Instead of finding higher entrepreneurial intentions in the business school, in which entrepreneurship education is more central, the study found that the students of the sports school had a greater tendency to start a business. The same is true in other industries, in which some studies have reported that male students have greater entrepreneurial intentions and seem to be more confident than women (Zarate-Hoyos and Larios-Meono, 2015; Bretones and Radrigan, 2018;Gavurova et al, 2018;Ndofirepi et al, 2018). However, it is not only female students who present lower levels of entrepreneurial intention but also students of both genders with no previous business experience (Hu and Ye, 2017).…”
Section: Clustereducation and Entrepreneurshipmentioning
confidence: 77%
“…Universities have an important formative role in addressing the gender equity issue, specifically through their mission of knowledge transfer and development of work tools, toward stimulating women’s self-confidence so that they would be encouraged to develop entrepreneurial initiatives (Zarate-Hoyos and Larios-Meono, 2015; Torres and Garcia, 2017; Bretones and Radrigan, 2018). Therefore, the continuous study of how higher education organizations are encouraging female entrepreneurship is necessary (Gavurova et al , 2018; Ndofirepi et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In South Africa where there is better exposure in terms of female liberation as against many other African countries in terms of gender disparity, studies have revealed that environmental and social factors in form of domestic responsibility of women, put them at a disadvantage over their male business adventurists as far as business ownership is concerned (Motilewa &Onakoya 2015 andVenter &Urban 2015). Ndofirepi et al (2018) further attributed social and environmental factors in form of education and skill acquisition to ownership and entrepreneurship participation in South Africa to tertiary institutions where it was affirmed that males are more willing to participate and own businesses than the female students. The result of the applied Mann-Whitney approach further advocated for social-driven policy that will encourage female participation and ownership for better and gender equality of business enterprises in South Africa.…”
Section: Social and Environmental Factorsmentioning
confidence: 99%
“…Entrepreneurship education molds entrepreneurial behavior and has been an essential factor for entrepreneurship development over the last decade (Bae et al, 2014). Entrepreneurship education able to enrich the proper psychological disposition includes subjective norms that produce an impact on entrepreneurial behavior (Ndofirepi et al, 2018). Individual attributes, family involvement, entrepreneurial education could affect the students' intention to become entrepreneurs positively and significantly (Mustapha and Selvaraju, 2015).…”
Section: The Relationship Between Entrepreneurship Education and Subjmentioning
confidence: 99%